Integrative Analysis of Metabolomic and Transcriptomic Data Reveals the Antioxidant Potential of Dietary Lutein in Chickens - Ren, Tuanhui; Lin, Wujian; He, Shizi; Yang, Xiuxian; Xian, Mingjian; Zhang, Zihao; Luo, Wen; Nie, Qinghua; Zhang, Xiquan (Frontiers in Veterinary Science, 2022)
Lutein can increase the body's skin color and has antioxidant potential. However, how it affects lipid metabolism and oxidative stress in chickens remains unknown. In this study, 74-day-old male chickens raised on feed supplemented with lutein had higher hip, back, breast, leg, shin and abdominal fat yellowness than the control group, and the livers of chickens in the lutein group had higher superoxide dismutase and glutathione peroxidase and lower malondialdehyde activities. To clarify the potential regulatory network regulated by lutein, we used RNA-seq and nontargeted metabolomics to detect changes in the male chicken liver and plasma, respectively. A total of 243 differentially expressed genes were significantly enriched in cytokine–cytokine receptor interaction signaling pathways, among others. A total of 237 significantly different metabolites were enriched in lysine biosynthesis and degradation and glycerophospholipid metabolism signaling pathways, among others. Finally, we comprehensively analyzed metabolome and transcriptome data and found that many differentially expressed genes and significantly different metabolites play crucial roles in lipid metabolism and oxidative stress. In summary, dietary lutein can improve male chicken skin yellowness and antioxidant indices and affect liver gene expression and plasma metabolites and may help improve the health of chickens.